A green recycled aggregate reinforced concrete

By processing waste rubber and construction waste into recycled aggregates and combining them with nano-microcrystalline cellulose and maleic anhydride grafted waste rubber powder, a green recycled aggregate reinforced concrete is prepared, which solves the problems of resource waste and environmental pollution, while reducing the demand for natural sand and gravel and protects the ecological environment.

CN116119984BActive Publication Date: 2025-03-28SUZHOU SHANGJIAN HANGXIN CONCRETE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211588087.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-03-28
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize waste rubber and construction waste, resulting in waste of resources and environmental pollution. At the same time, the concrete industry has a large demand for natural sand and gravel, which has led to the threat of the ecological environment.

Method used

A green recycled aggregate reinforced concrete was prepared by processing waste rubber and construction waste into recycled aggregates and combining them with nano-microcrystalline cellulose and maleic anhydride grafted waste rubber powder. The method includes scrap rubber crushing, microwave treatment and swelling reaction, grafting maleic anhydride, and melting and stirring with nano-microcrystalline cellulose and regenerated aggregate to form a modified regenerated aggregate.

Benefits of technology

Effectively consume a large amount of construction waste, improve urban appearance and environmental sanitation, reduce land encroachment during construction waste treatment, reduce environmental pollution, and at the same time reduce the demand for natural sand and gravel in the concrete industry, and protect the ecological environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides green recycled aggregate reinforced concrete, comprising the following raw materials in parts by weight: 50-90 parts of cement, 60-120 parts of natural sand, 20-30 parts of limestone, 30-60 parts of rubber modified recycled aggregate, 3-8 parts of water reducer, 5-12 parts of waste rubber powder, 5-12 parts of short-cut waste fiber and 30-50 parts of water, wherein the fineness modulus of natural sand is 2.1-2.7, the particle size of limestone is 10-25mm, the particle size of waste rubber powder is 1-3mm, and the length of short-cut fiber is 3-8cm. The present invention processes waste rubber and construction waste into recycled aggregate, partially or completely replaces natural aggregate to prepare recycled aggregate concrete, can effectively consume a large amount of construction waste, improve urban appearance and environmental sanitation, reduce the occupation of land in the process of construction waste treatment, and reduce environmental pollution; at the same time, the use of recycled aggregate can reduce the demand for natural sand and gravel in the concrete industry, thereby reducing the mining of natural sand and gravel and protecting the ecological environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete preparation methods, and in particular to green recycled aggregate reinforced concrete. Background Art

[0002] Among many solid wastes, a large amount of office waste paper poses a serious threat to the earth's ecological environment, because waste paper is usually not fully utilized and will eventually be disposed of by burning or slow degradation. It is reported that recycling one ton of waste paper is equivalent to cutting down 17 fewer trees, so recycling waste paper has both environmental and economic benefits. Recycled paper is an integral part of papermaking and pulping production, so waste paper recycling is an important means of waste paper recycling at this stage.

[0003] The composition of construction waste mainly includes slag, waste concrete blocks, waste mortar, brick and tile fragments, broken glass, broken tiles, waste asphalt blocks, waste plastics, waste metal materials and waste bamboo and wood, etc. Most of the construction waste, especially the construction waste generated by building demolition, can be reused as resources after sorting, removal or crushing. However, most of the construction waste in my country is not utilized at present. Instead, the construction waste is transported to the suburbs or villages and piled up or landfilled in the open air. The stacking or landfilling method for treating construction waste requires a large amount of arable land, and long-term stacking or landfilling will also pollute the soil, groundwater and atmosphere. Moreover, most of the construction waste is transported by non-enclosed transport vehicles. The problems of garbage spillage, dust and flying ash sand caused during transportation will also seriously affect the city appearance and environmental sanitation. It can be seen that the current treatment method of construction waste can no longer meet the needs of sustainable urban development, and the resource utilization of construction waste is imperative.

[0004] Rubber is a polymer solid. The increasing problem of waste rubber disposal is related to global environmental and resource issues. Waste rubber products are a kind of polymer elastic material that is difficult to dissolve under natural conditions. It is insoluble in water, difficult to dissolve in organic solvents, and not easy to rot. It is expensive to treat it according to traditional methods. Now the treatment method of rubber worldwide tends to recycle it. In the concrete industry, people often add rubber powder or rubber particles to concrete in a certain proportion to replace part of aggregate or cement, but the test results show that the mechanical properties of this concrete are greatly reduced. Summary of the invention

[0005] Technical problem to be solved: The purpose of the present invention is to provide a green recycled aggregate reinforced concrete, which processes waste rubber and construction waste into recycled aggregate, partially or completely replaces natural aggregate to prepare recycled aggregate concrete, which can effectively consume a large amount of construction waste, improve urban appearance and environmental sanitation, reduce the occupation of land in the process of construction waste treatment, and alleviate environmental pollution; at the same time, the use of recycled aggregate can reduce the demand for natural sand and gravel in the concrete industry, thereby reducing the exploitation of natural sand and gravel and protecting the ecological environment.

[0006] Technical solution: A green recycled aggregate reinforced concrete, comprising the following raw materials in parts by weight: 50-90 parts of cement, 60-120 parts of natural sand, 20-30 parts of limestone, 30-60 parts of rubber modified recycled aggregate, 3-8 parts of water reducer, 5-12 parts of waste rubber powder, 5-12 parts of short-cut waste fiber and 30-50 parts of water, wherein the fineness modulus of natural sand is 2.1-2.7, the particle size of limestone is 10-25 mm, the particle size of waste rubber powder is 1-3 mm, and the length of short-cut fiber is 3-8 cm.

[0007] Preferably, the rubber modified recycled aggregate is prepared by the following steps:

[0008] S1. The waste rubber was crushed to 100-300 mesh, subjected to microwave treatment for 30-60s, and the microwave-treated rubber powder was added to an ethanol solution of NaOH for swelling to obtain the swollen waste rubber powder;

[0009] S2. The waste rubber powder was placed in a rheometer and heated and mixed, and then maleic anhydride was added and mixed to obtain maleic anhydride grafted waste rubber powder;

[0010] S3. The waste paper material is broken and decomposed, firstly the paper material is crushed with a grinder, and then soaked in water and decomposed at a speed of 10000-15000r / min to obtain waste paper microfibers;

[0011] S4. The waste paper microfibers prepared in step S2 are dissolved in a sulfuric acid solution, heated and stirred in a water bath, the reaction is terminated, filtered and dried to obtain nanocrystalline cellulose, and the prepared nanocrystalline cellulose and maleic anhydride are melt-stirred to obtain maleic anhydride-grafted nanocrystalline cellulose;

[0012] S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution, and the regenerated aggregate is filtered by suction after immersion to obtain a modified regenerated aggregate;

[0013] S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, and after stirring, they are soaked and filtered with a solution containing nano-microcrystalline cellulose to obtain rubber powder modified aggregate.

[0014] Preferably, in step S2, the mass ratio of the waste rubber powder to maleic anhydride is 20:1-5, the mixing temperature of the waste rubber powder is 100-120° C., the mixing time is 5-10 min, and the mixing is continued for 5-10 min after the maleic anhydride is added.

[0015] Preferably, in step S4, the concentration of the sulfuric acid solution is 75-88 vt%, the temperature of the water bath is 50-60° C., the time is 1-4 h, and the mass ratio of maleic anhydride to nano-microcrystalline cellulose is 1:6-10.

[0016] Preferably, in step S5, the mass ratio of nano-crystalline cellulose to recycled aggregate is 1:5-10.

[0017] Preferably, in step S6, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:0.5-2.

[0018] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0019] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0020] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0021] Beneficial effects: The green recycled aggregate reinforced concrete and the preparation method thereof of the present invention have the following advantages:

[0022] 1. The present invention uses waste paper, waste rubber and waste construction waste as raw materials for concrete. Waste construction waste generally contains more pores and is not hydrophilic enough. In the present invention, waste paper is prepared into nano-microcrystalline cellulose, and the nano-microcrystalline cellulose is mixed with construction waste of a certain size, so that the surface and pores of the construction waste are fully adsorbed with the nano-microcrystalline cellulose. When the concrete is mixed in the later stage, the nano-microcrystalline cellulose can absorb water, reduce the pores in the aggregate of the waste construction waste, and improve the strength of the concrete;

[0023] 2. In order to improve the water absorption of rubber and the bonding effect with recycled building aggregates, the waste rubber is subjected to microwave treatment and swelling reaction, and maleic anhydride is grafted to improve the bonding effect between rubber and recycled building aggregates;

[0024] 3. The present invention processes waste rubber and construction waste into recycled aggregate, which partially or completely replaces natural aggregate to prepare recycled aggregate concrete, which can effectively consume a large amount of construction waste, improve urban appearance and environmental sanitation, reduce the occupation of land during the treatment of construction waste, and alleviate environmental pollution; at the same time, the use of recycled aggregate can reduce the demand for natural sand and gravel in the concrete industry, thereby reducing the exploitation of natural sand and gravel and protecting the ecological environment. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments:

[0026] Example 1

[0027] A rubber modified recycled aggregate is prepared by the following steps:

[0028] S1. The waste rubber was crushed to 100 mesh and microwaved for 60s, and the microwave-treated rubber powder was added to a 10wt% NaOH ethanol solution for swelling to obtain the swollen waste rubber powder;

[0029] S2. The waste rubber powder was placed in a rheometer for heating and mixing. The mixing temperature of the waste rubber powder was 120°C. The mixing time was 5 min. Then maleic anhydride was added. The mass ratio of the waste rubber powder to maleic anhydride was 4:1. After adding maleic anhydride, mixing was continued for 5 min to obtain maleic anhydride-grafted waste rubber powder.

[0030] S3. The waste paper material is broken and decomposed, first using a grinder to crush the paper material, and then soaked in water and decomposed at a speed of 15000r / min to obtain waste paper microfibers;

[0031] S4. dissolving the waste paper microfibers prepared in step S2 in a 75vt% sulfuric acid solution, heating and stirring in a water bath at a temperature of 50°C for 4 hours, terminating the reaction, filtering and drying to obtain nano-microcrystalline cellulose, and melting and stirring the prepared nano-microcrystalline cellulose and maleic anhydride, wherein the mass ratio of maleic anhydride to nano-microcrystalline cellulose is 1:6, to obtain nano-microcrystalline cellulose grafted with maleic anhydride;

[0032] S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution. After immersion, the regenerated aggregate is filtered by suction, and the mass ratio of the nanocrystalline cellulose to the regenerated aggregate is 1:5 to obtain a modified regenerated aggregate;

[0033] S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:2, and after stirring, the mixture is soaked and filtered with a solution containing nano-microcrystalline cellulose to obtain a rubber powder modified aggregate.

[0034] Example 2

[0035] A rubber modified recycled aggregate is prepared by the following steps:

[0036] S1. The waste rubber was crushed to 300 mesh and subjected to microwave treatment for 30s, and the microwave-treated rubber powder was added to a 5wt% NaOH ethanol solution for swelling to obtain the swollen waste rubber powder;

[0037] S2. The waste rubber powder was placed in a rheometer for heating and mixing. The mixing temperature of the waste rubber powder was 100 ° C. The mixing time was 10 min. Then maleic anhydride was added. The mass ratio of the waste rubber powder and maleic anhydride was 20:1. After adding maleic anhydride, mixing was continued for 10 min to obtain maleic anhydride grafted waste rubber powder.

[0038] S3. The waste paper material is broken and decomposed, first using a grinder to crush the paper material, and then soaked in water and decomposed at a speed of 10000r / min to obtain waste paper microfibers;

[0039] S4. dissolving the waste paper microfibers prepared in step S2 in a sulfuric acid solution having a concentration of 88vt%, heating and stirring in a water bath at a temperature of 60°C for 1 hour, terminating the reaction, filtering and drying to obtain nano-microcrystalline cellulose, and melting and stirring the prepared nano-microcrystalline cellulose and maleic anhydride, wherein the mass ratio of maleic anhydride to nano-microcrystalline cellulose is 1:10, to obtain nano-microcrystalline cellulose grafted with maleic anhydride;

[0040] S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution. After immersion, the regenerated aggregate is filtered by suction, and the mass ratio of the nanocrystalline cellulose to the regenerated aggregate is 1:10 to obtain a modified regenerated aggregate;

[0041] S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:0.5, and after stirring, the mixture is immersed and filtered with a solution containing nano-microcrystalline cellulose to obtain a rubber powder modified aggregate.

[0042] Example 3

[0043] A rubber modified recycled aggregate is prepared by the following steps:

[0044] S1. The waste rubber was crushed to 250 mesh and microwaved for 50s, and the microwave-treated rubber powder was added to a 8wt% NaOH ethanol solution for swelling to obtain the swollen waste rubber powder;

[0045] S2. The waste rubber powder was placed in a rheometer for heating and mixing. The mixing temperature of the waste rubber powder was 100 ° C. The mixing time was 8 min. Then maleic anhydride was added. The mass ratio of the waste rubber powder and maleic anhydride was 20:3. After adding maleic anhydride, mixing was continued for 8 min to obtain maleic anhydride grafted waste rubber powder.

[0046] S3. The waste paper material is broken and decomposed, firstly the paper material is crushed with a grinder, and then soaked in water and decomposed at a speed of 14000r / min to obtain waste paper microfibers;

[0047] S4. dissolving the waste paper microfibers prepared in step S2 in a sulfuric acid solution having a concentration of 80vt%, heating and stirring in a water bath at a temperature of 55°C for 2 hours, terminating the reaction, filtering and drying to obtain nano-microcrystalline cellulose, and melting and stirring the prepared nano-microcrystalline cellulose and maleic anhydride, wherein the mass ratio of maleic anhydride to nano-microcrystalline cellulose is 1:8, to obtain nano-microcrystalline cellulose grafted with maleic anhydride;

[0048] S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution. After immersion, the regenerated aggregate is filtered by suction, and the mass ratio of the nanocrystalline cellulose to the regenerated aggregate is 1:8 to obtain a modified regenerated aggregate;

[0049] S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:1, and after stirring, the mixture is immersed and filtered with a solution containing nano-microcrystalline cellulose to obtain a rubber powder modified aggregate.

[0050] In the following Examples 4-6, the rubber-modified recycled aggregate prepared in Examples 1-3 was added to concrete raw materials to prepare concrete.

[0051] Example 4

[0052] A green recycled aggregate reinforced concrete, comprising the following raw materials in parts by weight: 50 parts of cement, 60 parts of natural sand, 20 parts of limestone, 30 parts of rubber-modified recycled aggregate, 3 parts of water reducer, 5 parts of waste rubber powder, 5 parts of short-cut waste fiber and 30 parts of water, wherein the fineness modulus of the natural sand is 2.1, the particle size of the limestone is between 10-25 mm, the particle size of the waste rubber powder is between 1-3 mm, and the length of the short-cut fiber is between 3-8 cm (the above materials can be selected within this range);

[0053] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0054] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0055] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0056] Example 5

[0057] A green recycled aggregate reinforced concrete comprises the following raw materials in parts by weight: 90 parts of cement, 120 parts of natural sand, 30 parts of limestone, 60 parts of rubber-modified recycled aggregate, 8 parts of water reducer, 12 parts of waste rubber powder, 12 parts of short-cut waste fiber and 50 parts of water, wherein the fineness modulus of the natural sand is 2.7, the particle size of the limestone is 10-25 mm, the particle size of the waste rubber powder is 1-3 mm, and the length of the short-cut fiber is 3-8 cm;

[0058] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0059] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0060] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0061] Example 6

[0062] A green recycled aggregate reinforced concrete comprises the following raw materials in parts by weight: 70 parts of cement, 100 parts of natural sand, 20 parts of limestone, 40 parts of rubber-modified recycled aggregate, 5 parts of water reducer, 8 parts of waste rubber powder, 8 parts of short-cut waste fiber and 45 parts of water, wherein the fineness modulus of the natural sand is 2.4, the particle size of the limestone is 10-25 mm, the particle size of the waste rubber powder is 1-3 mm, and the length of the short-cut fiber is 3-8 cm;

[0063] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0064] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0065] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0066] Comparative Example 1

[0067] A green recycled aggregate reinforced concrete comprises the following raw materials in parts by weight: 70 parts of cement, 100 parts of natural sand, 20 parts of limestone, 40 parts of recycled aggregate, 5 parts of water reducer, 8 parts of waste rubber powder, 8 parts of short-cut waste fiber and 45 parts of water, wherein the fineness modulus of the natural sand is 2.4, the particle size of the limestone is 10-25 mm, the particle size of the waste rubber powder is 1-3 mm, and the length of the short-cut fiber is 3-8 cm;

[0068] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0069] S1. Weigh natural sand, limestone, recycled aggregate, water reducing agent, waste rubber powder and chopped waste fiber according to the specified weight ratio, mix them evenly to obtain a mixture;

[0070] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0071] Comparative Example 2

[0072] A rubber modified recycled aggregate is prepared by the following steps:

[0073] S1. The waste rubber was crushed to 250 mesh and microwaved for 50s, and the microwave-treated rubber powder was added to a 8wt% NaOH ethanol solution for swelling to obtain the swollen waste rubber powder;

[0074] S2. The waste rubber powder was placed in a rheometer for heating and mixing. The mixing temperature of the waste rubber powder was 100 ° C. The mixing time was 8 min. Then maleic anhydride was added. The mass ratio of the waste rubber powder and maleic anhydride was 20:3. After adding maleic anhydride, mixing was continued for 8 min to obtain maleic anhydride grafted waste rubber powder.

[0075] S3. Melting and stirring the recycled aggregate and the maleic anhydride grafted waste rubber powder prepared in step S2, wherein the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:1, and after stirring, obtaining rubber powder modified aggregate.

[0076] A green recycled aggregate reinforced concrete comprises the following raw materials in parts by weight: 75 parts of cement, 100 parts of natural sand, 20 parts of limestone, 30 parts of rubber-modified recycled aggregate, 5 parts of water reducer, 8 parts of waste rubber powder, 8 parts of short-cut waste fiber and 45 parts of water, wherein the fineness modulus of the natural sand is 2.4, the particle size of the limestone is 10-25 mm, the particle size of the waste rubber powder is 1-3 mm, and the length of the short-cut fiber is 3-8 cm;

[0077] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0078] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0079] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0080] Comparative Example 3

[0081] A rubber modified recycled aggregate is prepared by the following steps:

[0082] S1. The waste rubber was crushed to 250 mesh and microwaved for 50s, and the microwave-treated rubber powder was added to a 8wt% NaOH ethanol solution for swelling to obtain the swollen waste rubber powder;

[0083] S2. The waste rubber powder was placed in a rheometer for heating and mixing. The mixing temperature of the waste rubber powder was 100 ° C. The mixing time was 8 min. Then maleic anhydride was added. The mass ratio of the waste rubber powder and maleic anhydride was 20:3. After adding maleic anhydride, mixing was continued for 8 min to obtain maleic anhydride grafted waste rubber powder.

[0084] S3. The waste paper material is broken and decomposed, firstly the paper material is crushed with a grinder, and then soaked in water and decomposed at a speed of 14000r / min to obtain waste paper microfibers;

[0085] S4. The waste paper microfibers prepared in step S2 were dissolved in a sulfuric acid solution having a concentration of 80vt%, heated and stirred in a water bath at a temperature of 55°C for 2h, the reaction was terminated, and the nanocrystalline cellulose was obtained by filtration and drying;

[0086] S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution. After immersion, the regenerated aggregate is filtered by suction, and the mass ratio of the nanocrystalline cellulose to the regenerated aggregate is 1:8 to obtain a modified regenerated aggregate;

[0087] S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:1, and after stirring, a rubber powder modified aggregate is obtained.

[0088] A green recycled aggregate reinforced concrete comprises the following raw materials in parts by weight: 70 parts of cement, 100 parts of natural sand, 20 parts of limestone, 40 parts of rubber-modified recycled aggregate, 5 parts of water reducer, 8 parts of waste rubber powder, 8 parts of short-cut waste fiber and 45 parts of water, wherein the fineness modulus of the natural sand is 2.4, the particle size of the limestone is 10-25 mm, the particle size of the waste rubber powder is 1-3 mm, and the length of the short-cut fiber is 3-8 cm;

[0089] The method for preparing the green recycled aggregate reinforced concrete comprises the following steps:

[0090] S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the prescribed weight ratio, mix them evenly to obtain a mixture;

[0091] S2. Add water weighed in a weight ratio to the mixture in step S1, stir, and finally add cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

[0092] The compressive strength of green recycled aggregate reinforced concrete was tested using non-standard cubic test blocks of 100mm×100mm×100mm. The 3d, 7d and 28d compressive strength and splitting tensile strength under standard curing conditions were tested. The results are shown in the following table:

[0093]

[0094] It can be seen from the above table that the rubber modification method and the addition of nano-microcrystalline fibers prepared from waste paper have a great influence on the compressive strength and crack resistance of concrete.

[0095] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A green recycled aggregate reinforced concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 50-90 parts of cement, 60-120 parts of natural sand, 20-30 parts of limestone, 30-60 parts of rubber modified recycled aggregate, 3-8 parts of water reducing agent, 5-12 parts of waste rubber powder, 5-12 parts of short-cut waste fiber and 30-50 parts of water, wherein the fineness modulus of natural sand is 2.1-2.7, the particle size of limestone is 10-25 mm, the particle size of waste rubber powder is 1-3 mm, and the length of short-cut fiber is 3-8 cm; The rubber modified recycled aggregate is prepared by the following steps: S1 was added to an ethanol solution of NaOH for swelling to obtain the swollen waste rubber powder; S2. The waste rubber powder is placed in a rheometer for heating and mixing, and then maleic anhydride is added and mixed to obtain maleic anhydride grafted waste rubber powder; the mass ratio of waste rubber powder and maleic anhydride is 20:1-5, the mixing temperature of the waste rubber powder is 100-120 ° C, the mixing time is 5-10min, and the mixing is continued for 5-10min after the addition of maleic anhydride; S3. The waste paper material is broken and decomposed, the paper material is first crushed with a grinder, and then soaked in water and decomposed at a speed of 10000-15000r / min to obtain waste paper microfibers; S4. dissolving the waste paper microfibers prepared in step S3 in a sulfuric acid solution, heating and stirring in a water bath, terminating the reaction, filtering and drying to obtain nano-microcrystalline cellulose, and melting and stirring the prepared nano-microcrystalline cellulose and maleic anhydride to obtain maleic anhydride-grafted nano-microcrystalline cellulose; S5. The nanocrystalline cellulose prepared in step S4 is dissolved in water to obtain a cellulose solution, and the regenerated aggregate having a particle size range of 1.5-4.5 cm is selected and immersed in the cellulose solution, and the regenerated aggregate is filtered by suction after immersion to obtain a modified regenerated aggregate; S6. The modified recycled aggregate prepared in step S5 and the maleic anhydride grafted waste rubber powder prepared in step S2 are melted and stirred, and after stirring, they are soaked and filtered with a solution containing nano-microcrystalline cellulose to obtain rubber powder modified aggregate.

2. The green recycled aggregate reinforced concrete according to claim 1, characterized in that: In step S4, the concentration of the sulfuric acid solution is 75-88%, the temperature of the water bath is 50-60° C., the time is 1-4 hours, and the mass ratio of maleic anhydride to nano-microcrystalline cellulose is 1:6-10.

3. The green recycled aggregate reinforced concrete according to claim 1, characterized in that: In step S5, the mass ratio of nano-microcrystalline cellulose to recycled aggregate is 1:5-10.

4. The green recycled aggregate reinforced concrete according to claim 1, characterized in that: In step S6, the mass ratio of the modified recycled aggregate to the maleic anhydride grafted waste rubber powder is 10:0.5-2.

5. The method for preparing green recycled aggregate reinforced concrete according to claim 1, characterized in that: The following steps are involved: S1. Weigh natural sand, limestone, rubber-modified recycled aggregate, water-reducing agent, waste rubber powder and chopped waste fiber according to the specified weight ratio, mix them evenly to obtain a mixture; S2. adding water weighed in a weight ratio to the mixture in step S1, stirring, and finally adding cement in a specified weight ratio to obtain recycled aggregate reinforced concrete.

Citation Information

Patent Citations

  • Method for preparing cement mortar from waste rubber and bone meal

    CN105753415A

  • Polyurethane composite light aggregate concrete and preparation method thereof

    CN113292280A